Mastering Sport Anthropology: Redefining Sport Sciences Education - Elena Z Godina; Adu V Makhalin (Recent Research Advances in Arts and Social Studies Vol. 7, 2024)
The article discusses the content and the structure of a teaching program at Russian State University of Physical Education, Sport, Youth and Tourism (RSUPE)[1], realized in the 2010-2020, and the main directions of its suggested development in the system of sport education in Russia and elsewhere. An interdisciplinary field of study known as "sport anthropology," or "anthropology of sport," is rapidly expanding and incorporates a wide range of techniques and methodologies, including sociological, anthropological, genetic, psychological, and physiological ones. It builds a bridge between biological and cultural anthropology, and includes a lot of topics interesting not only for specialists in sport science and training but also for the general public. Among the most important issues are the following: influence of physical activity and different kinds of sports on growth and development of children (gender, age, ethnic aspects); obesity epidemics in the framework of changes in modern lifestyle; morphological and functional adaptations in sports of high qualification; genetic polymorphic systems associated with morphofunctional characteristics of athletes in different sport specializations; secular trends in sports – directions and differences from the general pattern, etc. The importance of the new program consists in giving new interdisciplinary approaches for problem-solving in the field of physical culture, education and sport training. It brings together methodology from different scientific disciplines: anthropology, genetics, psychology, physiology, sociology, etc. The program consisted of two years of studies, and was structured as lecture courses and practical seminars in major disciplines of biological anthropology and applied sciences. The impact of the program could be evaluated in terms of much broader perspectives of the alumni’s in the knowledge of major bioanthropology theories and application of its methods in their future practical work as coaches, trainers and sport scientists.